Assessing Racial and Ethnic Discrimination in Children: A Scoping Review of Available Measures for Child Health Disparities Research (Mary Ann Liebert, 2021)
Objectives: To characterize the availability, content, and psychometric properties of self-reported measures that assess race/ethnicity-related discrimination or psychosocial stress and have potential relevance to studies of health disparities in children and adolescents. Design: Using PRISMA extension guidelines for scoping reviews, we searched Ovid Medline, CINAHL, PsychInfo, and Scopus databases from 1946 to April 20, 2020, using the search terms ?stress,? ?child,? ?adolescents,? ?discrimination,? and ?psychometrics.? We limited the search to articles in English, with children and adolescents, in the United States. For each measure, we extracted information about the content, reliability, and construct validity. Results: The 12 measures that met inclusion criteria assessed discrimination or stress from racial discrimination in African American children and adolescents (n=8), acculturative stress in Hispanic/Latino children (n=1), or bicultural stress in Mexican American adolescents (n=2), and one measure assessed both discrimination-related and acculturative stress in Hispanic/Latino children. The majority (n=7) articles were published between 2001 and 2010. All discrimination measures evaluated individual experiences of discrimination and one also evaluated stressfulness of discrimination and coping. The acculturative stress measures assessed general stress and immigration-related discrimination, and the bicultural stress measures evaluated many different aspects of biculturalism. Conclusions: Despite the recent increased interest in the racial discrimination and stress as a contributor to racial or ethnic health disparities affecting U.S. children and adolescents, the small number of eligible measures identified and incomplete coverage of various types of racial and ethnic discrimination within and across population groups indicates a currently inadequate capacity to conduct child health disparity studies on this issue.